Correlation between Electronic Structure and Electron Conductivity in MoX2 X = S, Se, Te) - Saifful Kamaluddin, Muzakir (2016)

(untitled)
Layered structure molybdenum dichalcogenides, MoX2 (X = S, Se, and Te) are in focus as reversible charge storage electrode for pseudocapacitor applications. Correlation between number of layer and bandgap of the materials has been established by previous researchers. The correlation would reveal a connection between the bandgap and charge storage properties i.e., amount of charges that could be stored, and speed of storage or dissociation. In this work, fundamental parameters viz., (i) size-offset between a monolayer and exciton Bohr radius of MoX2 and (ii) ground and excited state electron density have been studied. We have identified realistic monolayer models of MoX2 using quantum chemical calculations which explain a correlation between size-offset and charge storage properties. We conclude that as the size-offset decreases, the higher possibility of wave functions overlap between the excited state, and ground state electrons; therefore the higher the electron mobility, and conductivity of the MoX2 would be.